3D supramolecular networks of Mn(II)-5-sulfosalicylate assembled with 4, 4′-dipyridyl N, N′-dioxide and 4, 4′-dipyridyl: Structure, photoluminescence and DFT calculations. (29th March 2015) - Mistri, Soumen; Zangrando, Ennio; Farnetti, Erica; Manna, Subal Chandra
Graphical abstract: The supramolecular complexes {[Mn2 (HSsal)2 (dpyo)3 (H2 O)6 ]·2(H2 O)} (1 ) and {[Mn(4, 4′-bipy)(H2 O)4 ]·(HSsal)·(H2 O)} n (2 ) [dpyo = 4, 4′-dipyridyl N, N ′-dioxide; 4, 4′-bipy = 4, 4′-bipyridine and HSsal = 5-sulfosalicylate dianion] have been synthesized and characterized. The intense fluorescence of the complexes was tested in association with several aromatic compounds. The experimental structural results have been supported by DFT calculations. Abstract: The supramolecular complexes {[Mn2 (HSsal)2 (dpyo)3 (H2 O)6 ]·2(H2 O)} (1 ) and {[Mn(4, 4′-bipy)(H2 O)4 ]·(HSsal)·(H2 O)} n (2 ) [dpyo = 4, 4′-dipyridyl N, N ′-dioxide; 4, 4′-bipy = 4, 4′-bipyridine and HSsal = 5-sulfosalicylate dianion] have been synthesized and structurally characterized. Complex1 is a rare Mn dinuclear species realized with bridging dpyo and coordinated HSsal ligands to form a 3D architecture through H-bonding and π⋯π interactions. In complex2, Mn(H2 O)4 fragments are bridged by 4, 4′-bipy, giving rise to a 1D chain. The adjoining chains encapsulate HSsal anions to give a 3D structure through a R 2 2 (12) H-bonding synthon and π⋯π interactions. The complexes were tested in association with several aromatic compounds, since they exhibit intense fluorescence ( λ ex  = 223 nm, λ em  = 308, 325, 353 and 393 nm for1 ; λ ex  = 237 nm, λ em  = 312, 335, 348 and 394 nm for2 ). The outcome of DFT calculations on model compounds is discussed and compared with the experimental X-ray structural data.